Spanish for mastery - Valette, Jean Paul.; Hanley, Teresa Carrera; Olaya, Clara Ines.; Suarez-Richard, Frederick 1941-.; Valette, Rebecca M. (Lexington, Mass. D.C. Heath, 1980)
A high school text providing an introduction to the language and culture of the Spanish-speaking world.
Keywords: Spanish language -- Grammar -- 1950- .